The pediatric misophonia and hyperacusis questionnaire (PMHQ): a screening tool inspired by the MisoQuest and hyperacusis questionnaire. - Carson, Tana B.; Medina, Angela M.; Qiu, Yuxi; Long, Katherine L.; Niebles, Monica; Palacio-Raine, Alexandra; Saenz, Taylor (International Journal of Audiology, 2025)
Objective: Decreased Sound Tolerance (DST) conditions often emerge in childhood, making early identification and treatment important. This paper details the development and validation of the Paediatric Misophonia and Hyperacusis Questionnaire (PMHQ), a dual DST parent-report screening tool intended to provide early identification of misophonia and hyperacusis among children with and without autism age 6-17 years. Study designs and samples: Three studies were completed including (1) content development with input from audiology experts (n = 9) and parents of children with DST conditions (n = 20); (2) content revision to improve relevance to autism with input from parents of children with autism (n = 15); and (3) psychometric analysis of item characteristics of the PMHQ based on responses from parents of children age 6-17 years (n = 200). Results: The PMHQ-4 demonstrates adequate psychometric properties at the item level (item discrimination, difficulty, item information function) and at the test level (test information function). A definitive version of the PMHQ with recommended cut-off scores for each subscale is provided. Conclusions: The resulting PMHQ-4 is a 14-item screening tool comprised of 8 misophonia and 6 hyperacusis items. The PMHQ-4 can provide a valid measure of misophonia and hyperacusis for children age 6-17 years. Further evaluation is warranted in clinical DST samples.